Marketing Plan for SILC Lasic Center - Ratih Pratiwi; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Ratna Indrawati (Journal of Multidisciplinary Academic, 2019)
Lasic is a permanent solution to overcome refractive disorders in humans. In Indonesia, the general eye hospital is providing lasic surgery as well as other related procedures. The absence of special clinics that exclusively serve lasic, in addition to the imbalance between the number of patients with refraction disorders who have been treated with lasic surgery and the popular notion that lasic procedures are expensive, offers a business opportunity to open a lasic-specialized clinic which will be named SILC Lasic Center. SILC Lasic Center will offer cost-effective lasic surgery with flexible payment programs while still prioritizing quality and patient safety. In order to introduce and expose SILC Lasic Center so that the community takes notice, there needs to be a proper marketing plan so that the purpose of SILC Lasic Center will be in accordance with its vision and its mission can be achieved.